A smart gas leakage monitoring system for use in hospitals - Nadia Mahmood Hussien; Yasmin Makki Mohialden; Nada Thanoon Ahmed; Mostafa Abdulghafoor Mohammed; Tole Sutikno (Institute of Advanced Engineering and Science, 2020)
A gas leaks lead to personal and financial damage. Much effort has been dedicated to preventing such leaks and developing reliable techniques for leak detection and leakage localization using sensors. These sensors usually sound an alarm after detecting a dangerous gas in its vicinity. This paper describes a system for detecting a gas leakage from cylinders which notifies the user via the GSM network. The system consists of an LPG gas leakage detector which sends a warning signal to Arduino Uno Microcontroller. The system uses the GSM network to send notifications, a liquid crystal display (LCD) monitor to display the warning message and buzzer to sound the alert.